A Glance At Furnitur Bertutur: A Temporary Exhibition At Jakarta History Museum - Perdana, Aditya Bayu; Syahid, Mush'ab 'Abdu Asy (Badan Riset dan Inovasi Nasional (BRIN), 2025)
The Furnitur Bertutur exhibition, held at the Jakarta History Museum from October 2024 to January 2025, presents an overview of Dutch East Indies or Indies style furniture as a manifestation of material encounters and hybridity between European and Nusantaran societies in colonial Jakarta/Batavia. This exhibition showcases various types of historical furniture mostly from the Verenigde Oostindische Compagnie (VOC) period, such as chairs, tables, and cabinets, highlighting craftsmanship and cross-cultural influences mirroring the multi-layered history of Jakarta. This paper aims to inquire the exhibition practice while providing constructive criticism regarding its substance from critical museology, art history and interior architecture perspectives. The method used is a comparative architectural criticism, involving direct observation towards the exhibition’s presentation, an analysis of its narrative and displayed information, spatial layout, and curatorial approach, then compare them with relevant historical and theoretical references. The exhibition manages to display the richness of Indies furniture in an attractive and engaging setting. The integration of digital catalogue as explanatory medium is effective and the catalogue itself is well designed. There are however notable shortcomings. In the display space, several items seemed to be out of scope thematically and chronologically, while reconstructed rooms show anachronistic elements that may misled casual observers. In its narrative, some of the omitted information obscure the exhibition’s scope, as well as crucial aspects of Batavian live which could have enhanced understanding of the displayed pieces. Some statements seem to contradict referenced sources and are not sufficiently discussed, giving the negative impression of a didactic revision. Nevertheless, this exhibition deserves appreciation for reigniting interests in Indies furniture as a complex historical heritage. Some of its significant elements have the potential to be preserved as part of the museum’s permanent exhibition.